The development of route learning in Down syndrome, Williams syndrome and typical development: investigations with virtual environments. Issue 4 (5th October 2014) - Purser, Harry R.M.; Farran, Emily K.; Courbois, Yannick; Lemahieu, Axelle; Sockeel, Pascal; Mellier, Daniel; Blades, Mark
Abstract The ability to navigate new environments has a significant impact on the daily life and independence of people with learning difficulties. The aims of this study were to investigate the development of route learning in Down syndrome (N = 50), Williams syndrome (N = 19), and typically developing children between 5 and 11 years old (N = 108); to investigate use of landmarks; and to relate cognitive functions to route‐learning ability in these groups. Overall, measures of attention and long‐term memory were strongly associated with route learning, even once non‐verbal ability was controlled for. All of the groups, including 5‐ to 6‐year‐old TD children, demonstrated the ability to make use of all landmark types to aid route learning; those near junctions, those further from junctions, and also distant landmarks (e.g. church spire, radio mast). Individuals with WS performed better than a matched subset of TD children on more difficult routes; we suggest that this is supported by relatively strong visual feature recognition in the disorder. Participants with DS who had relatively high levels of non‐verbal ability performed at a similar level to TD participants.